2014
DOI: 10.1097/mbp.0000000000000069
|View full text |Cite
|
Sign up to set email alerts
|

Intrafamilial aggregation and heritability of office−day blood pressure difference in a community of African ancestry

Abstract: Although office and ambulatory BP may show similar heritability estimates, genetic associations with carefully determined office BP measurements may be confounded by the heritability of office-day BP differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“… 16 Within South Africa, data are also emerging that BP is heritable across families (parent–child and sibling–sibling pairs). 17 However, due to the high levels of hypertension in South African adults, hypertension in a family member is unlikely on its own to be a sensitive enough indicator to identify at-risk young adults or children for intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 Within South Africa, data are also emerging that BP is heritable across families (parent–child and sibling–sibling pairs). 17 However, due to the high levels of hypertension in South African adults, hypertension in a family member is unlikely on its own to be a sensitive enough indicator to identify at-risk young adults or children for intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of monozygotic and dizygotic twins have shown high heritability of systolic blood pressure (SBP) and diastolic blood pressure (DBP) in populations of both African and European decent,14 15 though heritability may be lower for individuals of African decent 16. Within South Africa, data are also emerging that BP is heritable across families (parent–child and sibling–sibling pairs) 17. However, due to the high levels of hypertension in South African adults, hypertension in a family member is unlikely on its own to be a sensitive enough indicator to identify at-risk young adults or children for intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of mono- and dizygotic twins have shown high heritability of systolic and diastolic blood pressure in populations of both African and European decent 12 13 , though heritability may be lower for individuals of African decent 14 . Within South Africa, data is also emerging that blood pressure is heritable across families (parent-child, and sibling pairs) 15 . However, due to the high levels of hypertension in South African adults, hypertension in a family member is unlikely on its own to be a sensitive enough indicator to identify at risk young adults or children for intervention..…”
Section: Introductionmentioning
confidence: 99%